New clinical and experimental insights into Old World and neotropical ocular toxoplasmosis (2014)
Retinal lesions or other ocular manifestations are serious consequences of infection with the protozoan parasite Toxoplasma gondii. Whilst classically considered a consequence of congenital transmission, recent screening studies estimated that 2% of T. gondii seropositive persons in Europe and North America have retinal lesions, most of them persisting unnoticed. The situation is more dramatic in South America, probably due to the predominance of virulent strains. Some of these strains seem to exhibit ocular or neuronal tropism and are responsible for severe ocular lesions. Despite the medical importance, the physiopathological mechanisms have only recently begun to be elucidated. The particular immune-privileged situation in the eye has to be considered. Studies on French patients showed low or undetectable ocular parasite loads, but a clear Th1/Th17 type immune reaction. Suitable mouse models have appeared in the last few years. Using such a model, IL-17A proved to impair parasite control and induce pathology. In contrast, in South American patients, the parasite seems to be much less efficiently controlled through a Th2 type or suppressive immune response that favors parasite replication. Finally, several host genetic markers controlling immune response factors have been associated with ocular involvement of T. gondii infection, mainly in South America. © 2013 Australian Society for Parasitology Inc.